The LIM motif defines a specific zinc-binding protein domain. - Michelsen, J W (1993)
The cysteine-rich protein (CRP) contains two copies of the LIM sequence motif, CX2CX17HX2CX2CX2CX17-CX2C, that was first identified in the homeodomain proteins Lin-11, Is1-1, and Mec-3. The abundance and spacing of the cysteine residues in the LIM motif are reminiscent of a metal-binding domain. We examined the metal-binding properties of CRP isolated from chicken smooth muscle (cCRP) and from a bacterial expression system and observed that cCRP is a specific Zn-binding metalloprotein. Four Zn(II) ions are maximally bound to cCRP, consistent with the idea that each LIM domain coordinates two metal ions. From spectroscopic studies of Co(II)- and 113Cd(II)-substituted cCRP, we determined that each metal ion is tetrahedrally coordinated with cysteinyl sulfurs dominating the ligand types. One metal site within each LIM motif has tetrathiolate (S4) coordination, the second site may either be S4 or S3N1. The LIM motif represents another example of a specific Zn-binding protein sequence.